OUTPUT-INPUT RATIO OF TECHNICAL SYSTEMS AND GAS PIPELINES - Грудз, Ярослав Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Chronicle of establishment of notion of output-input ratio of machines and technical systems is conducted and on the basis of its analysis the expedience and necessity of introduction of notion of output-input ratio is shown for main gas pipelines as difficult and energy capacity technical systems. The methods of determination of output-input ratio of the gas-transport system are offered taking into account the losses of energy in gas repumping aggregates over and linear areas.